Performance regulation and control method for additive manufacturing aluminum-silicon alloy

Al-Si alloy components were prepared through the selected laser melting process and performed direct aging heat treatment, which solved the problem of difficult balance of thermal conductivity and mechanical strength of aluminum-silicon alloys in additive manufacturing, and achieved a combination of high thermal conductivity and high mechanical strength .

CN119457126AActive Publication Date: 2025-02-18NORTHWESTERN POLYTECHNICAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411646793.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

In the prior art, aluminum-silicon alloys are difficult to balance thermal conductivity and mechanical strength during additive manufacturing, resulting in insufficient stability of the radiator when facing mechanical stress.

Method used

Al-Si alloy components were prepared by selective laser melting technology and directly aged heat treatment was performed. By increasing the substrate preheating temperature to reduce residual stress, retain the mesh tissue characteristics, and promote solid-solution atom precipitation.

Benefits of technology

It effectively improves the thermal conductivity and mechanical strength of aluminum-silicon alloys, meeting the needs of lightweight and high-efficiency radiators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457126A_ABST
    Figure CN119457126A_ABST
Patent Text Reader

Abstract

The invention discloses a performance regulation and control method for additive manufacturing of an aluminum-silicon alloy, and belongs to the technical field of aluminum alloy additive manufacturing. The performance regulation and control method comprises the following steps that S1, Al-Si alloy powder is prepared; s2, the Al-Si alloy powder is subjected to a selective laser melting process to form a component; s3, direct aging heat treatment is conducted on the component; the microstructure of the additive manufacturing Al-Si alloy is improved through direct aging heat treatment, and the heat conductivity coefficient of the alloy is improved while the alloy is endowed with superior mechanical strength. The method can be used for solving the problem of heat dissipation of high-power devices existing at present, and has great significance in development of efficient and light radiators and application of the radiators in the related fields of aerospace, automobiles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum alloy additive manufacturing, and specifically relates to a performance control method for additively manufacturing aluminum silicon alloy. Background Art

[0002] With the acceleration of industrialization and the continuous increase in the power density of electronic devices, the heat dissipation of instruments and equipment has become more challenging. However, due to the limitations of traditional manufacturing methods such as casting and machining, the complex structural design of the heat sink is restricted, making it difficult to further improve the heat dissipation efficiency. Metal additive manufacturing technology brings higher degrees of freedom to the lightweight design and manufacturing of heat sinks, and is particularly suitable for the forming and preparation of complex structures such as heterogeneous, structural integration, and lattice structures.

[0003] Thermal conductivity and strength are two key performance indicators in heat sink design; although thermal conductivity is generally considered to be the primary material property that determines heat sink performance. However, in the application of additive manufacturing processes, the importance of mechanical strength is more prominent. High mechanical strength not only ensures the stability of the heat sink in the face of various mechanical stresses, but also allows the use of thinner wall thickness designs. This design can increase the heat exchange area and shorten the heat transfer path, significantly improving the overall performance of the heat sink.

[0004] Aluminum alloys are used as thermal conductive materials due to their low density, high specific strength, corrosion resistance, and excellent electrical and thermal conductivity. The thermal conductivity of the 6063 deformed aluminum alloy, which is currently widely used in thermal management structures, is about 200W / (m·K) at room temperature, but its additive manufacturing formability is poor; while the selective laser melting of eutectic / near-eutectic aluminum-silicon alloys has good processability and is widely used in the field of additive manufacturing. The uniqueness of the non-equilibrium solidification of the selective laser melting process leads to excellent mechanical strength of Al-Si alloys, but their thermal conductivity is much lower than that of cast alloys with the same composition, and they also produce large residual stresses. At present, T6 or post-annealing heat treatment is usually used for components.

[0005] However, both of the above heat treatments will destroy the network structure characteristics produced by the selective laser melting process, greatly reduce the mechanical strength, and thus affect the use of formed heat sinks with thin walls. How to balance the thermal conductivity and mechanical strength of the alloy is an important issue currently faced by lightweight and efficient heat sinks. Summary of the invention

[0006] In order to overcome the above-mentioned deficiencies in the prior art, the present invention aims to provide a performance control method for additively manufactured aluminum-silicon alloys to solve the problem of difficulty in balancing thermal conductivity and mechanical strength in the prior art.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: A method for controlling the performance of an additively manufactured aluminum-silicon alloy comprises the following steps: S1: preparing Al-Si alloy powder; S2: Based on the Al-Si alloy powder, a selective laser melting process is adopted to form a component; S3: performing aging heat treatment on the component.

[0008] A further improvement of the present invention is: Preferably, in S1, the Al-Si alloy powder has a composition, in mass percentage, of Si content of 9-11wt%, Mg content of 0.20-0.45wt%, Fe content ≤0.55wt%, Mn content ≤0.45wt%, and the balance is Al.

[0009] Preferably, in S1, Al-Si alloy powder is prepared by vacuum gas atomization process.

[0010] Preferably, in S1, the particle size specification of the Al-Si alloy powder is 15um-53um.

[0011] Preferably, in S2, during the selective laser melting process, the laser power is 330-350 W; and the laser scanning speed is 1300-1500 mm / s.

[0012] Preferably, in S2, during the selective laser melting process, the laser scanning spot spacing is 0.12-0.14 mm; and the spot diameter is 0.08 mm.

[0013] Preferably, in S2, during the selective laser melting process, the forming layer height is 0.03 mm; and the scanning path adopts a unidirectional scanning path.

[0014] Preferably, in S2, during the selective laser melting process, the substrate preheating temperature is 80°C.

[0015] Preferably, in S3, the direct aging heat treatment is to place the component in a heat preservation furnace for heating, the heat preservation temperature is: 180°C-200°C, the heat preservation time is 8-10h, and then air-cooling to room temperature after heat preservation.

[0016] Preferably, the tensile strength of the Al-Si alloy component after direct aging heat treatment is 350-410 MPa, and the thermal conductivity reaches 160-175 W / (m·K).

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a performance control method for additively manufactured aluminum-silicon alloys. The method first prepares Al-Si alloy powder according to the target construction composition, and after the Al-Si alloy powder is used to prepare a component through a selective laser melting process, the component is directly subjected to an aging heat treatment operation. The method combines the selective laser melting process with the heat treatment technology, reduces the residual stress generated during the forming process by increasing the preheating temperature of the substrate, and provides an ideal deposited microstructure for the subsequent heat treatment steps. Common annealing heat treatment and T6 heat treatment usually destroy the network structure characteristics of the deposited alloy and form large-sized polygonal Si particles, thereby causing great damage to the mechanical properties of the alloy. The present invention adopts a direct aging heat treatment process, which can effectively retain the network structure characteristics generated during the selective laser melting forming process, promote the precipitation of solid solution atoms, and reduce the negative impact on the thermal conductivity of the alloy. Through this optimization treatment, the mechanical strength of the alloy is maintained at a high level, while the thermal conductivity of the alloy is significantly improved, thereby meeting the needs of related engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Secondary electron image of the deposited Al-Si alloy formed by selective laser melting provided in the example of the present invention.

[0019] Figure 2 A low-magnification secondary electron image of the direct-aging state of an Al-Si alloy formed by selective laser melting provided as an example of the present invention.

[0020] Figure 3 A high-magnification secondary electron image of the direct-aging state of an Al-Si alloy formed by selective laser melting provided in an example of the present invention.

[0021] Figure 4 The room temperature tensile stress-strain curves of the Al-Si alloy formed by selective laser melting in the deposited state and the direct aged state provided in the examples of the present invention. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0023] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0024] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0025] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0026] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0027] The present invention discloses a method for controlling the performance of an additively manufactured aluminum-silicon alloy, the method comprising the following steps: S1: preparing hypoeutectic Al-Si alloy powder; The composition of the Al-Si alloy powder, in terms of mass percentage, includes 9-11wt% Si; 0.20-0.45wt% Mg; ≤0.55wt% Fe; ≤0.45wt% Mn; and the balance is Al.

[0028] Al-Si alloy powder is prepared by vacuum gas atomization process. The particle size of Al-Si alloy powder is 15μm-53μm. The powder is prepared by vacuum gas atomization, and this process is carried out under vacuum or inert gas protection to avoid alloy oxidation and contamination. The molten alloy liquid is rapidly cooled and solidified into tiny particles by high-pressure gas spray to form Al-Si alloy powder with the required particle size. The particle size range of the powder is controlled between 15μm and 53μm. This size range is conducive to the subsequent selective laser melting process, ensuring good powder fluidity and spreadability, as well as density and precision after melting.

[0029] S2: forming a component by a selective laser melting process on the hypoeutectic Al-Si alloy powder; The process parameters of selective laser melting are as follows: laser power is 330-350W; laser scanning speed is 1300-1500mm / s; laser scanning spot spacing is 0.12-0.14mm; forming layer height is 0.03mm; spot diameter is 0.08mm; and the scanning path adopts a unidirectional scanning path.

[0030] In this process, limiting the laser power can ensure sufficient energy input to melt the powder while avoiding defects caused by overheating. Limiting the laser scanning speed can control the melting rate and cooling rate, affecting the microstructure and performance of the component.

[0031] Preferably, the substrate preheating temperature during the selective laser melting process is 80°C.

[0032] S3: performing direct aging heat treatment on the component.

[0033] The process parameters of direct aging heat treatment are: 180℃-200℃ for 8-10h, then air-cooled to room temperature. Direct aging heat treatment is a heat treatment process that improves the microstructure and properties of the alloy by heating and keeping it warm for a period of time, followed by natural cooling to room temperature. This step is particularly critical for Al-Si alloy components prepared by SLM, because it can effectively release the residual stress generated during the printing process and promote the formation of precipitation phases, thereby improving strength and hardness while maintaining good thermal conductivity.

[0034] After aging heat treatment, the final microstructure still retains the characteristics of the deposited mesh structure. This mesh structure is mainly composed of Al-Si eutectic phase, and its morphology is dense or dispersed long strip mesh structure. These mesh structures divide the Al matrix into multiple regions, thus forming a unique microstructure. The mesh structure helps to improve the tensile strength of the alloy because of its role in hindering dislocations.

[0035] The tensile strength of Al-Si alloy components after direct aging heat treatment is 350-410MPa, and the thermal conductivity reaches 160-175W / (m·K).

[0036] The following is further described in conjunction with specific embodiments.

[0037] Example 1 A method for controlling the thermal conductivity of an additively manufactured hypoeutectic Al-Si alloy comprises the following steps: S1: The vacuum gas atomization method is used to prepare the hypoeutectic Al-Si alloy powder. The composition of the obtained hypoeutectic Al-Si alloy powder is as follows: in mass percentage, 10.06 wt% Si, 0.311 wt% Mg, 0.082 wt% Fe, 0.01 wt% Mn, and the balance is Al; the particle size of the obtained hypoeutectic Al-Si alloy powder is 13um-53um.

[0038] S2: The hypoeutectic Al-Si alloy powder is subjected to the selective laser melting process to form components; during the selective laser melting forming process, the selected laser power is 340W; the laser scanning speed is 1400mm / s; the laser scanning spot spacing is 0.13mm; the forming layer height is 0.03mm; the spot diameter is 0.08mm; the scanning path adopts a unidirectional scanning path; and the substrate preheating temperature is 80°C.

[0039] S3: Direct aging heat treatment is performed on the formed component; the selected direct aging heat treatment process parameters are: keep at 200℃ for 10h, and then air cool to room temperature. The tensile strength and thermal conductivity of the alloy in the direct aging state are 350MPa and 173.7 W / (m·K), respectively.

[0040] See also Figure 1 The microstructural characteristics of the deposited aluminum-silicon alloy formed by selective laser melting are shown. The figure shows a dark α-Al matrix and a gray eutectic Si phase distributed in a network around the matrix.

[0041] See also Figure 2 and Figure 3 The microstructural changes of the aluminum-silicon alloy formed by selective laser melting after direct aging treatment are shown at different magnifications. After aging heat treatment, the network structure characteristics of the alloy are still retained, and granular and rod-shaped nanoscale precipitation phases formed by Si element precipitation appear in the α-Al matrix. The precipitation of Si element effectively reduces the lattice distortion of the α-Al matrix, thereby improving the thermal conductivity of the alloy.

[0042] See also Figure 4 The room temperature tensile stress-strain curves of the deposited and directly aged alloys in Example 1. Due to the network structure characteristics and the presence of nano-precipitated phases, a good tensile strength of the alloy can still be obtained.

[0043] Example 2 A method for controlling the thermal conductivity of an additively manufactured hypoeutectic Al-Si alloy comprises the following steps: S1: The vacuum gas atomization method is used to prepare the hypoeutectic Al-Si alloy powder. The composition of the obtained hypoeutectic Al-Si alloy powder is as follows: in mass percentage, 10.06 wt% Si, 0.311 wt% Mg, 0.082 wt% Fe, 0.01 wt% Mn, and the balance is Al; the particle size of the obtained hypoeutectic Al-Si alloy powder is 13um-53um.

[0044] S2: The hypoeutectic Al-Si alloy powder is subjected to the selective laser melting process to form components; during the selective laser melting forming process, the selected laser power is 340W; the laser scanning speed is 1400mm / s; the laser scanning spot spacing is 0.13mm; the forming layer height is 0.03mm; the spot diameter is 0.08mm; the scanning path adopts a unidirectional scanning path; and the substrate preheating temperature is 80°C.

[0045] S3: Direct aging heat treatment is performed on the formed component; the selected direct aging heat treatment process parameters are: keep at 180℃ for 10h, and then air cool to room temperature. The tensile strength and thermal conductivity of the alloy in the direct aging state are 399MPa and 163.8 W / (m·K), respectively.

[0046] Example 3 A method for controlling the thermal conductivity of an additively manufactured hypoeutectic Al-Si alloy comprises the following steps: S1: The vacuum gas atomization method is used to prepare the hypoeutectic Al-Si alloy powder. The composition of the obtained hypoeutectic Al-Si alloy powder is as follows: in mass percentage, 10.06 wt% Si, 0.311 wt% Mg, 0.082 wt% Fe, 0.01 wt% Mn, and the balance is Al; the particle size of the obtained hypoeutectic Al-Si alloy powder is 13um-53um.

[0047] S2: The hypoeutectic Al-Si alloy powder is subjected to the selective laser melting process to form components; during the selective laser melting forming process, the selected laser power is 340W; the laser scanning speed is 1400mm / s; the laser scanning spot spacing is 0.13mm; the forming layer height is 0.03mm; the spot diameter is 0.08mm; the scanning path adopts a unidirectional scanning path; and the substrate preheating temperature is 80°C.

[0048] S3: Direct aging heat treatment is performed on the formed component; the selected direct aging heat treatment process parameters are: keep at 180℃ for 8h, and then air cool to room temperature. The tensile strength and thermal conductivity of the alloy in the direct aging state are 409MPa and 160.4W / (m·K), respectively.

[0049] Example 4 A method for controlling the thermal conductivity of an additively manufactured hypoeutectic Al-Si alloy comprises the following steps: S1: The vacuum gas atomization method is used to prepare the hypoeutectic Al-Si alloy powder. The composition of the obtained hypoeutectic Al-Si alloy powder is as follows: in mass percentage, 10.06 wt% Si, 0.311 wt% Mg, 0.082 wt% Fe, 0.01 wt% Mn, and the balance is Al; the particle size of the obtained hypoeutectic Al-Si alloy powder is 13um-53um.

[0050] S2: The hypoeutectic Al-Si alloy powder is subjected to the selective laser melting process to form components; during the selective laser melting forming process, the selected laser power is 340W; the laser scanning speed is 1400mm / s; the laser scanning spot spacing is 0.13mm; the forming layer height is 0.03mm; the spot diameter is 0.08mm; the scanning path adopts a unidirectional scanning path; and the substrate preheating temperature is 80°C.

[0051] S3: Direct aging heat treatment is performed on the formed component; the selected direct aging heat treatment process parameters are: keep at 190℃ for 10h, and then air cool to room temperature. The tensile strength and thermal conductivity of the alloy in the direct aging state are 378MPa and 168.8 W / (m·K), respectively.

[0052] Example 5 A method for controlling the thermal conductivity of an additively manufactured hypoeutectic Al-Si alloy comprises the following steps: S1: The vacuum gas atomization method is used to prepare the hypoeutectic Al-Si alloy powder. The composition of the obtained hypoeutectic Al-Si alloy powder is as follows: in mass percentage, 10.06 wt% Si, 0.311 wt% Mg, 0.082 wt% Fe, 0.01 wt% Mn, and the balance is Al; the particle size of the obtained hypoeutectic Al-Si alloy powder is 13um-53um.

[0053] S2: The hypoeutectic Al-Si alloy powder is subjected to the selective laser melting process to form components; during the selective laser melting forming process, the selected laser power is 330W; the laser scanning speed is 1300mm / s; the laser scanning spot spacing is 0.12mm; the forming layer height is 0.03mm; the spot diameter is 0.08mm; the scanning path adopts a unidirectional scanning path; and the substrate preheating temperature is 80°C.

[0054] S3: Direct aging heat treatment is performed on the formed component; the selected direct aging heat treatment process parameters are: keep at 190℃ for 8h, and then air cool to room temperature. The tensile strength and thermal conductivity of the alloy in the direct aging state are 388MPa and 164.6W / (m·K), respectively.

[0055] Example 6 A method for controlling the thermal conductivity of an additively manufactured hypoeutectic Al-Si alloy comprises the following steps: S1: The vacuum gas atomization method is used to prepare the hypoeutectic Al-Si alloy powder. The composition of the obtained hypoeutectic Al-Si alloy powder is as follows: in mass percentage, 10.06 wt% Si, 0.311 wt% Mg, 0.082 wt% Fe, 0.01 wt% Mn, and the balance is Al; the particle size of the obtained hypoeutectic Al-Si alloy powder is 13um-53um.

[0056] S2: The hypoeutectic Al-Si alloy powder is subjected to the selective laser melting process to form components; during the selective laser melting forming process, the selected laser power is 350W; the laser scanning speed is 1500mm / s; the laser scanning spot spacing is 0.14mm; the forming layer height is 0.03mm; the spot diameter is 0.08mm; the scanning path adopts a unidirectional scanning path; and the substrate preheating temperature is 80°C.

[0057] S3: Direct aging heat treatment is performed on the formed component; the selected direct aging heat treatment process parameters are: keep at 200℃ for 8h, and then air cool to room temperature. The tensile strength and thermal conductivity of the alloy in the direct aging state are 364MPa and 170.2W / (m·K), respectively.

[0058] Example 7 A method for controlling the thermal conductivity of an additively manufactured hypoeutectic Al-Si alloy comprises the following steps: S1: The vacuum gas atomization method is used to prepare the hypoeutectic Al-Si alloy powder. The composition of the obtained hypoeutectic Al-Si alloy powder is as follows: in mass percentage, 10.06 wt% Si, 0.311 wt% Mg, 0.082 wt% Fe, 0.01 wt% Mn, and the balance is Al; the particle size of the obtained hypoeutectic Al-Si alloy powder is 13um-53um.

[0059] S2: The hypoeutectic Al-Si alloy powder is subjected to the selective laser melting process to form components; during the selective laser melting forming process, the selected laser power is 330W; the laser scanning speed is 1400mm / s; the laser scanning spot spacing is 0.14mm; the forming layer height is 0.03mm; the spot diameter is 0.08mm; the scanning path adopts a unidirectional scanning path; and the substrate preheating temperature is 80°C.

[0060] S3: Direct aging heat treatment is performed on the formed components; the selected direct aging heat treatment process parameters are: keep at 200℃ for 9h, and then air cool to room temperature. The tensile strength and thermal conductivity of the alloy in the direct aging state are 354MPa and 171.3W / (m·K), 350MPa and 173.7 W / (m·K), 358MPa and 170.2 W / (m·K) respectively. The above descriptions are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for controlling the performance of an additively manufactured aluminum-silicon alloy, characterized in that: The following steps are involved: S1: preparing Al-Si alloy powder; S2: Based on the Al-Si alloy powder, a selective laser melting process is adopted to form a component; S3: performing aging heat treatment on the component.

2. The method for controlling the performance of aluminum-silicon alloys in additive manufacturing according to claim 1, characterized in that: In S1, the Al-Si alloy powder has a Si content of 9-11 wt%, a Mg content of 0.20-0.45 wt%, a Fe content of ≤0.55 wt%, a Mn content of ≤0.45 wt%, and the balance is Al.

3. The performance control method for additively manufacturing aluminum-silicon alloy according to claim 1, characterized in that: In S1, Al-Si alloy powder is prepared by vacuum gas atomization process.

4. The performance control method for additively manufacturing aluminum-silicon alloy according to claim 3, characterized in that: In S1, the particle size specification of the Al-Si alloy powder is 15um-53um.

5. The method for controlling the performance of aluminum-silicon alloys in additive manufacturing according to claim 1, characterized in that: In S2, during the selective laser melting process, the laser power is 330-350W; the laser scanning speed is 1300-1500mm / s.

6. The method for controlling the performance of aluminum-silicon alloys in additive manufacturing according to claim 1, characterized in that: In S2, during the selective laser melting process, the laser scanning spot spacing was 0.12-0.14 mm; the spot diameter was 0.08 mm.

7. The method for controlling the performance of aluminum-silicon alloys in additive manufacturing according to claim 1, characterized in that: In S2, during the selective laser melting process, the forming layer height is 0.03 mm; the scanning path adopts a unidirectional scanning path.

8. The method for controlling the performance of aluminum-silicon alloys in additive manufacturing according to claim 1, characterized in that: In S2, during the selective laser melting process, the substrate preheating temperature is 80°C.

9. The method for controlling the performance of aluminum-silicon alloys in additive manufacturing according to claim 1, characterized in that: In S3, the direct aging heat treatment is to place the component in a heat preservation furnace for heating at a temperature of 180°C-200°C for a time of 8-10 hours, and then air-cool to room temperature after heat preservation.

10. The method for controlling the performance of aluminum-silicon alloy in additive manufacturing according to claim 1, characterized in that: The tensile strength of Al-Si alloy components after direct aging heat treatment is 350-410MPa, and the thermal conductivity reaches 160-175W / (m·K).

Citation Information

Patent Citations

  • High Fe content Al-Mg2Si alloy prepared by laser selective melting and preparation method

    CN110760724A

  • Laser additive and heat treatment composite process for high-strength and high-toughness aluminum-silicon alloy or composite material thereof

    CN112536446A

  • Powder material with high thermal conductivity

    CN116723904A

  • Preparation method for optimizing aluminum-silicon alloy performance based on selective laser melting

    CN118559036A

  • METHOD FOR PRODUCING A THREE-DIMENSIONAL ALUMINUM ALLOY PART

    DE102019106979A1